Running brave - Benson, Robby 1956-; Hingle, Pat; Cron, Claudia; Bean, Henry ca. 20. Jh; Hendryx, Shirl (Trinity Home Entertainment, 2004)
Story of real-life Olympic champion Billy Mills. From life on an impoverished South Dakota Indian reservation to his phenomenal upset victory at the 1964 Olympic Games in Tokyo, Mills constantly challenged the barriers of culture and his own deeply-rooted insecurities